Caught in the Low-Skills Training Trap - Jane Cruikhank (Adult Education Research Conference, 2007)
With the 1998 signing of the Canada-Saskatchewan Labour Market Development Agreement, the federal government devolved EI training to the province. This roundtable session looks at the type of training being delivered and raises some issues that currently are being explored.